Esophageal Perforation and EVAC in Pediatric Patients: A Case Series of Four Children - Ritz, Laura Antonia; Hajji, Mohammad Samer; Schwerd, Tobias; Koletzko, Sibylle; von Schweinitz, Dietrich; Lurz, Eberhard; Hubertus, Jochen (Frontiers in Pediatrics, 2021)
Introduction: In pediatric patients, esophageal perforation (EP) is rare but associated with significant morbidity and mortality rates of up to 20–30%. In addition to standard treatment options, endoscopic esophageal vacuum-assisted closure (EVAC) therapy has shown promising results, especially in adult patients. Thus far, the only data on technical success and effectiveness of EVAC in pediatric patients were published by Manfredi et al. at Boston Children’s Hospital (1,2). The sparse data on EVAC in children indicates that this promising technique has been barely utilized in pediatric patients. More data are needed to evaluate efficacy and outcomes of this technique in pediatric patients. Method: We reviewed five cases of therapy using EVAC, ArgyleTM Replogle Suction Catheter (RSC), or both on pediatric patients with EP in our institution between October 2018 and April 2020. Results: Five patients with EP (median 3.4 years; 2 males) were treated with EVAC, RSC, or a combination. Complete closure of EP was not achieved after EVAC alone, though patients’ health stabilized and inflammation and size of EP decreased after EVAC. Four patients then were treated with RSC until the EP healed. One patient needed surgery as the recurrent fistula did not heal sufficiently after 3 weeks of EVAC therapy. Two patients developed stenosis and were successfully treated with dilatations. One patient treated with RSC alone showed persistent EP after five weeks. Conclusion: EVAC in pediatric patients is technically feasible and a promising method to treat EP, regardless of the underlying cause. EVAC therapy can be terminated as soon as local inflammation and C-reactive protein levels decrease, even if the mucosa is not healed completely at that time. A promising subsequent treatment is RSC. An earlier switch to RSC can substantially reduce the need of anesthesia during subsequent treatments. Our findings indicate that EVAC is more effective than RSC alone. In some cases, EVAC can be used to improve the tissues condition in preparation for a re-do surgery. At 1 year after therapy, all but one patient demonstrated sufficient weight gain. Further prospective studies with a larger cohort are required to confirm our observations from this small case series.